2016
DOI: 10.1186/s12969-016-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the MTHFR gene are not associated with Methotrexate intolerance in patients with juvenile idiopathic arthritis

Abstract: BackgroundMethotrexate (MTX) intolerance is a frequent problem of long-term treatment in juvenile idiopathic arthritis (JIA). Mutations in the methylentetrahydrofolate reductase (MTHFR) gene may increase toxicity of MTX, potentially constituting an initial stimulus for this conditioned response. The objective of this study was to investigate the relationship of common MTHFR gene mutations and occurrence of MTX intolerance in pediatric patients with JIA treated with MTX.MethodsConsecutive JIA patients on at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This Danish version of the MISS had a high internal consistency in the JIA group, indicating the Danish translation of the MISS was satisfactory and supporting other studies in the MISS being easy to adapt to a new language [1517]. For the ALL group the analysis of internal consistency questioned whether the behaviour domain fits properly with the remaining MISS.…”
Section: Discussionsupporting
confidence: 74%
“…This Danish version of the MISS had a high internal consistency in the JIA group, indicating the Danish translation of the MISS was satisfactory and supporting other studies in the MISS being easy to adapt to a new language [1517]. For the ALL group the analysis of internal consistency questioned whether the behaviour domain fits properly with the remaining MISS.…”
Section: Discussionsupporting
confidence: 74%
“…MTX intolerance as a unified construct of the anticipatory and associative side effects associated with prolonged use of MTX has only recently been described, and the MISS questionnaire tries to capture this construct [ 7 ]. So far, genetic studies have been unsuccessful in finding a causal link to MTX intolerance [ 5 , 23 , 24 ]. Interaction between the patient and his parents, physicians and other caregivers as well as psychological and social background factors can all influence frequency and severity of MTX intolerance symptoms, and therefore the efficacy of any intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with low-dose MTX therapy exhibits few serious adverse effects; treatment is usually discontinued due to intolerance symptoms such as anticipatory nausea and refusal to take the medication [ 3 , 4 ]. The origin of MTX intolerance is still unclear, and common countermeasures have been shown to be ineffective in suppressing MTX intolerance [ 5 , 6 ]. Current studies demonstrate high rates of intolerance for JIA patients on treatment with low-dose MTX, while high-dose regimens e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SNP in its gene are widely researched and believed to contribute to reduced enzymatic activity. The role of MTHFR rs1801131 is not consistent; in a study on RA, it was associated with toxicity 34 , but some studies found different or no association 5,10,13,32 . To our knowledge, ABCC2 rs2273697 and rs2804402 have not yet been evaluated in relation to MTX treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In the previous pharmacogenetic studies in patients with JIA, AE were not assessed and not subdivided according to the organ system or severity 8,11,12,31,32 , or only a limited number of SNP were analyzed 13,14,33 . Identifying patients with AE that make them discontinue MTX would be of major clinical importance.…”
Section: Discussionmentioning
confidence: 99%